НОРМАТИВНО-ТЕХНІЧНЕ РЕГУЛЮВАННЯ ЯКОСТІ НАПРУГИ В ЕЛЕКТРИЧНИХ МЕРЕЖАХ З ДЖЕРЕЛАМИ РОЗОСЕРЕДЖЕНОЇ ГЕНЕРАЦІЇ - Жаркін , А.Ф.; Новський , В.О.; Палачов , С.О. (Інститут електродинаміки НАН України, Київ, 2016)
The object of analysis is current state of Ukrainian and international regulations concerning voltage quality in power grids with distributed generation. The analysis of European experience suggests measures that will contribute to broad implementation in Ukraine of renewable energy electric generators without compromising the voltage quality in power grids. References 3.